VARIASI DAN FUNGSI RAGAM BAHASA IKLAN LAYANAN MASYARAKAT DI MEDIA SOSIAL PADA MASA PANDEMI COVID-19 SUATU TINJAUAN SOSIOLINGUISTIK - Anisa Dimas Tutik (Balai Bahasa Sulawesi Tengah, 2021)
ABSTRACTThis research is motivated by the problems contained in public service advertisements on social media during the covid-19 pandemic. The objectives of the research are (1) to describe the form of language variations of public service advertisements on social media during the Covid-19 pandemic. (2) To describe the function of the various languages of public service advertisements on social media during the Covid-19 pandemic. The method used is descriptive qualitative by explaining objects based on facts contained in public service advertisements on social media during the covid-19 pandemic. The data source of this research is public service advertisements on social media. Data collection techniques used were recording techniques and data transcripts in the form of words, phrases, and sentences in public service advertisements. The data analysis techniques used in this study include data collection, data reduction, data presentation, and conclusions. The results of this study indicate that there are as many as 3 types of language variations in terms of speakers, usage and formality. There are 5 types of language functions, namely emotive, referential, directive, poetic, and fatigued